Prosocial behavior and positive psychology - Arias Gallegos, Walter (2015)
The article makes a review about the concept of prosocial behavior, its origin from social psychology, its foundations and theoretical explanations related to positive psychology. The production over positive psychology in Lima and Arequipa, as well as the models of intervention based on prosocial behavior and positive emotions are analyzed in a brief way.